Impact of Knowledge Spillovers on Firm Innovation: The Mediation Role of Organizational Culture and Moderation of Technological Advancements - Khaled Milod Khalifa Hudoud; Hatim Ramadhan Mohammed Alzayani (المجلة الأفروآسيوية للبحث العلمي, 2024)
This study examines the impact of knowledge spillovers on firm innovation, emphasizing the mediating role of organizational culture and the moderating influence of technological advancements. Knowledge spillovers, which occur when firms gain access to external knowledge through interactions within their industry or community, are pivotal for fostering innovation. However, the effectiveness of these spillovers is often contingent upon the organizational culture that governs how knowledge is shared and utilized within firms. We propose that a supportive organizational culture enhances the positive effects of knowledge spillovers on innovative outcomes by promoting collaboration and knowledge integration. Furthermore, the role of technological advancements is explored as a moderator; as technology evolves, its capacity to facilitate or hinder knowledge transfer can significantly impact the relationship between spillovers and innovation. Using a mixed-methods approach, we analyze data from various industries to assess these dynamics. Our findings suggest that firms with a strong, adaptive organizational culture and advanced technological capabilities are better positioned to leverage knowledge spillovers for innovation. The study concludes with implications for managers and policymakers aiming to foster an environment conducive to innovation through strategic cultural and technological initiatives.